Multi odd–even effects on cell parameters, melting points, and optical properties of chiral crystal solids based on S-naproxen - Tang, Gui-Mei; Wang, Jin-Hua; Zhao, Chao; Wang, Yong-Tao; Cui, Yue-Zhi; Cheng, Fei-Yue; Ng, Seik Weng (Royal Society of Chemistry, 2015)
A set of chiral crystal solids with odd and even numbers of carbon atoms based on S-naproxen, ester S-naproxen-R1 (R1 = H, methyl, ethyl, n-propyl, n-butyl, and n-amyl), has been prepared, alternatively crystallizing in the space groups P21 and P212121, respectively, which shows the multi odd-even effects on cell parameters, melting points, and optical properties.